Greening rice-fallow areas: integrating pulses and oilseeds for sustainable cropping in eastern India - Rakesh Kumar; Anup Das; Surajit Mondal; Pravin Kumar Upadhyay; Bhagwati Prasad Bhatt; Janki Sharan Mishra; Anil Kumar Singh; Jaipal Singh Choudhary; Sanjeev Kumar; Prem Kumar Sundaram; Ashis Kumar Biswas; Sanjay Singh Rathore; et al. (Frontiers in Sustainable Food Systems)
Rice-fallow areas, widespread in rainfed rice-growing regions of South Asia, remain uncultivated during the post-rainy (winter) season due to multiple challenges, including inadequate irrigation infrastructure, cultivation of long-duration rice varieties, and soil moisture imbalances. South Asia has approximately 22.3 million hectares of rice-fallow land, with India contributing the largest share (88.3%). Eastern Indian states, which account for 82% of India’s rice-fallow area, presents significant opportunities for cropping intensification. However, several constraints—such as biotic (pest and disease), abiotic stresses (temperature extremes, drought, etc.), rapid soil moisture depletion, and disturbances from free-grazing livestock-hinder efforts to cultivate a second crop, perpetuating poverty among the small and marginal farmers. Introducing stress-tolerant rabi crops, particularly pulses (chickpea, lentil, lathyrus, field pea) and oilseeds (mustard, toria, safflower, linseed), offers a promising solution to enhance system productivity and improve the farmers’ livelihoods. Policymakers have recently increased the public investment in rice-fallows intensification, yet fragmented and ad-hoc initiatives often fail to deliver sustainable outcomes due to complex and multidimensional challenges involved. This study critically examines the key issues affecting rice-fallow lands and provides strategic recommendations to convert these underutilized areas into the productive cropping systems during winter and spring. Additionally, it reviews Central and State Government programs related to rice-fallow management, emphasizing the need for research to align with ongoing policy initiatives for maximum impact. The findings of this study offers a valuable insights for the policymakers, planners, and stakeholders, highlighting the potential of pulses and oilseeds to enhance the food security, reduce poverty, and promote sustainable, climate-resilient agricultural production systems in the region.